Masjid Pathok Negara Mlangi; Penjaga Islam Sunni Di Yogyakarta - Latifah, Zuhrotul; Maimunah, Siti; -, Riswinarno (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract: This research examines the role of the Pathok Negoro Mlangi Mosque in preserving Sunni Islam in Yogyakarta. This mosque, also known as Masjid Jami’ An Nur, is closely related to the Yogyakarta Palace because it was built by Prince Hangabehi Sandiyo or Kiai Nur Iman, who was the elder brother of Sultan Hamengku Buwono I in 1758. The research questions addressed in this study are: What is the background of the establishment of the Pathok Negoro Mlangi Mosque? What is the role of the Pathok Negoro Mlangi Mosque in preserving Sunni teachings? This research employs the concept of the mosque as a center of Islamic culture. The research method used is historical methodology with four stages: heuristic, verification, interpretation, and historiography. The results of this research indicate that the Pathok Negoro Mlangi Mosque was built by Kiai Nur Iman, the brother of Sultan Hamengku Buwono I, who chose to spread the religion or preach rather than hold positions in the palace with all its luxuries. On the land granted by Sultan Hamengku Buwono I, Kiai Nur Iman built a mosque to teach the religion of Sunni Islam. The studies conducted at the Mlangi mosque are based on books aligned with Ahlu al-Sunnah wa al-Jama’ah, such as Matan Taqrib, Fathu al-Wahhab bi Syarh Manhaj al-Thullab Syarh Minhaj al-Thalibin wa ‘Umdah al-Muftin, Fathu al-Mu’in bi Syarhi Qurrathi al-‘Ain bi Muhimmat al-Din, tafsir Al-Jalalain, the hadith books Sahih Bukhari and Sahih Muslim, and the book Riyadl al-Shalihin. Regarding ethical issues, the study books include Ta’lim al-Muta’allim Thariq al-Ta’allum and Ihya’ ‘Ulum al-Din, books that integrate the beliefs of Ahlu al-Sunnah wa al-Jama’ah, the Shafi'i fiqh school, and the Sufism of Ahlu al-Sunnah wa al-Jama’ah. Studies of these books continue to be preserved by the successive generations of Kiai Nur Iman in various regions of Yogyakarta.Abstrak: Penelitian ini mengkaji tentang peran Masjid Pathok Negoro Mlangi dalam melestarikan Islam Sunni di Yogyakarta. Masjid ini juga dikenal sebagai Masjid Jami’ An Nur yang berkaitan erat dengan Keraton Yogyakarta karena dibangun oleh Pangeran Hangabehi Sandiyo atau Kiai Nur Iman yang merupakan kakak dari Sultan Hamengku Buwono I pada tahun 1758. Permasalahan penelitian ini adalah bagaimana latar belakang berdirinya Masjid Pathok Negoro Mlangi? Bagaimana peran Masjid Pathok Negoro Mlangi dalam melestarikan ajaran Sunni? Penelitian ini menggunakan konsep masjid sebagai pusat kebudayaan Islam. Metode penelitiannya adalah metode sejarah dengan empat tahap, yaitu heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian ini bahwa Masjid Pathok Negoro Mlangi dibangun oleh Kiai Nur Iman yang merupakan kakak Sultan Hamengku Buwono I, lebih memilih menyebarkan agama atau berdakwah daripada menduduki jabatan di keraton dengan segala kemewahannya. Di tanah perdikan pemberian Sultan Hamengku Buwono I, Kiai Nur Iman membangun masjid untuk mengajarkan agama Islam Ahlu al-Sunnah wa al-Jama’ah. Kajian kitab di masjid Mlangi adalah kitab-kitab yang berhaluan Ahlu al-Sunnah wa al-Jama’ah seperti Matan Taqrib, Fathu al-Wahhab bi Syarh Manhaj al-Thullab Syarh Minhaj al-Thalibin wa ‘Umdah al-Muftin, Fathu al-Mu’in bi Syarhi Qurrathi al-‘Ain bi Muhimmat al-Din, tafsir Al-Jalalain, kitabhadis Shahih Bukhari,Shahih Muslim dan kitab Riyadl al-Shalihin, dalam persoalan akhlak kajian kitabnya adalah kitab Ta’lim al-Muta’allim Thariq al-Ta’allum, dan kitab Ihya’ ‘Ulum al-Din, kitab yang mengintegrasikan antara akidah Ahlu al-Sunnah wa al-Jama’ah, fiqh mazhab Syafii, dan tasawuf Ahlu al-Sunnah wa al-Jama’ah. Kajian-kajian kitab semacam ini terus dilestarikan oleh generasi penerus Kiai Nur Iman di berbagai wilayah Yogyakarta.